Non-English Major Teachers’ Pedagogical Readiness in Elementary English Instruction: An Interpretative Phenomenological Study in Indonesia - Uas Gna; Yupika Maryansyah (Yayasan Sembilan Pemuda Indonesia, 2026)
Following the enactment of Permendikbudristek No. 12 of 2024, which establishes English as a compulsory subject in Indonesian elementary schools, increasing attention has been directed toward the pedagogical readiness of non-English major teachers who are expected to teach English despite limited specialized preparation. While previous studies have primarily examined teacher competence and classroom challenges, limited research has explored how pedagogical readiness is experienced and enacted by non-English major teachers within this new policy context. This study aimed to explore the pedagogical readiness of non-English major teachers in teaching English to young learners at private elementary schools in Bengkulu City. Using an Interpretative Phenomenological Analysis (IPA) design, data were collected through semi-structured interviews and classroom observations involving ten non-English major teachers. The findings revealed that pedagogical readiness was manifested across seven pedagogical competencies, although considerable variation existed among participants. Teachers encountered challenges related to English language proficiency, implementing child-centered instruction, lesson planning, classroom interaction, and formative assessment. Their readiness was influenced by individual factors, including teaching experience and self-efficacy, as well as contextual factors such as professional development opportunities and institutional support. This study contributes to the growing literature on teacher readiness by demonstrating that pedagogical readiness is a dynamic, context-dependent construct that extends beyond pedagogical competence and is shaped by the interaction between teachers’ professional capabilities and their instructional environment.